Open surgical approach of a rare giant renal artery aneurysm - Thomas Kotsis, MD, PhD; Aikaterini Kotzadimitriou, MD; Panagitsa Christoforou, MD, PhD (Journal of Vascular Surgery Cases and Innovative Techniques, 2025)
Renal artery aneurysm (RAA) is a rare entity that challenges vascular surgeons. We report the case of a 75-year-old male patient with a rare, giant 8 cm RAA and the open surgical approach after a failed endovascular attempt. Resection of the RAA and an aortorenal bypass with a polytetrafluoroethylene graft were performed by exteriorizing the left kidney to expose the renal hilum. We discuss the pros and cons of the attempt to help decision-making in similar RAA complex cases and the role of a multidisciplinary team to achieve the best result.